Blockade of high mobility group box 1 augments antitumor T‐cell response induced by peptide vaccination as a co‐adjuvant. Issue 12 (18th December 2016) - Waki, Kayoko; Yamada, Akira
Abstract : High mobility group box 1 (HMGB1) is a member of the family of damage‐associated molecular patterns, which cause inflammation and trigger innate immunity through Toll‐like receptors 2/4 and the receptor for advanced glycation end products. We examined the effect of glycyrrhizin, a selective inhibitor of HMGB1, on the induction of CTLs in mice. B6 mice, either OT‐1 spleen cell‐transferred or untransferred, were immunized with an s.c. injection of OVA257–264 peptide with topical imiquimod, and glycyrrhizin was mixed with the antigen peptide. Proliferation of OT‐1 cells after immunization was enhanced by glycyrrhizin. The effect of glycyrrhizin was confirmed in other adjuvant systems, such as CpG oligonucleotide and monophosphoryl lipid A, but glycyrrhizin was not effective in Freund's incomplete adjuvant system. The augmenting effects of glycyrrhizin were also observed in other synthetic HMGB1 inhibitors, gabexate mesilate, nafamostat, and sivelestat. Thus, the effects are common to the HMGB1 inhibitors. Induction of CTLs detected by γ‐interferon enzyme‐linked immunospot assay was similarly augmented by glycyrrhizin. In a therapeutic vaccine model, glycyrrhizin inhibited the growth of s.c. transplanted EG.7 tumors. Expression of inflammatory cytokines in the skin inoculation site was downregulated by glycyrrhizin. These results suggest that HMGB1 inhibitors might be useful as a co‐adjuvant for peptide vaccination with an innate immunity receptor‐related adjuvant. Abstract : We demonstrated that selective inhibitors of HMGB1, a member of DAMPs and also known as an initiation factor of inflammation, augmented anti‐tumor immunity through inhibition of inflammation related cytokines. HMGB1 inhibitors might be useful for peptide vaccination with an innate immunity receptor‐related adjuvant.